Gender and Criminal Justice Responses to Terrorism in the United States - Jackson, Summer M. (Crime & delinquency, 2023)
Generally, women receive more lenient treatment by the criminal justice system compared to men. Prior research on how gender shaped prosecutorial decision-making and sentencing outcomes has focused on conventional forms of crime, while less is known about how it operates in terrorism-related cases. This is a critical gap in a growing body of research on justice disparities given that women continue to make up a significant portion of terrorism defendants in the U.S. Utilizing data from the American Terrorism Study, we seek to answer how legal and extralegal case attributes of federal terrorism cases vary across gender, how gender shapes federal terrorism case outcomes, and how combinations of relevant case attributes uniquely impact court outcomes for males and females.